Nihāyat al-marām fī dirāyat al-kalām - Rāzī, Fakhr al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
Ḍiyāʾ al-Dīn al-Makkī (d. 559/1163-64) was a specialist of theology and law and the preacher ( khaṭīb ) of the Shāfi'ī congregation in Rayy of his time. Ḍiyāʾ al-Dīn is, however, best known as the father of the famous theologian and critic of Avicenna (d. 428/1037), Fakhr al-Dīn Rāzī (d. 606/1210), often referred to as Ibn al-Khaṭīb, certainly in his younger years. Ḍiyāʾ al-Dīn studied Ashʿarī theology in Nishapur under Abu ʼl-Qāsim b. Salmān al-Anṣārī (d. 512/1118), himself a student of Imām al-Ḥaramayn al-Juwaynī (d. 478/1085). Besides, he also studied in Marwarūdh, hometown of the Shāfiʿī jurist al-Ḥusayn b. Masʿūd al-Farrāʾ al-Baghawī (d. 516/1122). The work of which the one remaining volume is published here is one of the largest works in early Ashʿarī theology. It gives a fine impression of the discussions around some of the main differences between the Muʿtazila and the Ashʿarīs, besides its importance as a source of his son's ideas.